Approaches to Learning for the ANZCA Final Examination and Validation of the Revised Study Process Questionnaire in Specialist Medical Training. Issue 5 (September 2013) - Weller, J. M.; Henning, M.; Civil, N.; Lavery, L.; Boyd, M. J.; Jolly, B.
When evaluating assessments, the impact on learning is often overlooked. Approaches to learning can be deep, surface and strategic. To provide insights into exam quality, we investigated the learning approaches taken by trainees preparing for the Australian and New Zealand College of Anaesthetists (ANZCA) Final Exam. The revised two-factor Study Process Questionnaire (R-SPQ-2F) was modified and validated for this context and was administered to ANZCA advanced trainees. Additional questions were asked about perceived value for anaesthetic practice, study time and approaches to learning for each exam component. Overall, 236 of 690 trainees responded (34%). Responses indicated both deep and surface approaches to learning with a clear preponderance of deep approaches. The anaesthetic viva was valued most highly and the multiple choice question component the least. Despite this, respondents spent the most time studying for the multiple choice questions. The traditionally low short answer questions pass rate could not be explained by limited study time, perceived lack of value or study approaches. Written responses suggested that preparation for multiple choice questions was characterised by a surface approach, with rote memorisation of past questions. Minimal reference was made to the ANZCA syllabus as a guide for learning. These findings indicate that, although trainees found the exam generally relevant to practice and adopted predominantly deep learning approaches, there was considerable variation between the four components. These results provide data with which to review the existing ANZCA Final Exam and comparative data for future studies of the revisions to the ANZCA curriculum and exam process.